(untitled) (Revista Brasileira Multidisciplinar, 2023)
Antiresorptive are potent inhibitors of bone resorption widely used in the treatment of osteoporosis and bone metabolism diseases associated or not with neoplasias. Due to their efficacy, anti-resorptives such as bisphosphonates (BPs) are largely prescribed. However, these medications have been associated with several side effects, such as, Medication Related Osteonecrosis of the Jaws (MRONJ). In a literature review, we observed a lack of knowledge by health professionals, regarding this pathology. Considering these data, this current review aims to provide these professionals, especially physicians and dental surgeons, a better understanding of the BPs, their types, mechanisms of action in the bone tissue and metabolism, possible side effects, especially BRONJ, methods for its prevention and treatment. In addition, data regarding knowledge of physicians, dental surgeons and patients about BPs were also collected. To carry out the bibliographic survey, Pubmed, Scieloand Google Academic databases were used and articles published from 1981 to 2022 were selected. From the literature data, it can be concluded that BPs reduce bone resorption mainly by directly inhibiting osteoclasts. Despite its effectiveness in the treatment of bone pathologies, BPs can lead to alterations in the gastrointestinal tract, renal toxicity, alterations in the eye region, and bone osteonecrosis, especially the MRONJ. The knowledge of the MRONJ by health professionals is still restricted, and this seems to be associated with a deficiency in the instruction of the users of the BPs, regarding the problem. Even in the face of several treatment types proposed in the literature, MRONJ still presents difficult resolution. Therefore, its prevention is extremely relevant. In order to prevent it, the interaction between doctors, dentists and patients needs to be better established. In this paper, besides guidelines for dentists, physicians and students from these areas, techniques to mitigatin the risk and to treat MRONJ are proposed for dentists. KEYWORDS: bisphosphonates; knowledge; bone resorption; osteoclast; osteonecrosis of the jaws.